The genus Lolia from freshwater habitats in Egypt with one new species - Abdel-Aziz, Faten A. (Phytotaxa, 2016)
A new species of Lolia and the sexual morph of L. aquatica are described, with illustrations, from decayed submerged wood in the River Nile, Egypt. Molecular phylogenetic analyses of partial SSU and LSU rDNA sequence data place the sexual morph of L. aquatica and the new species, L. dictyospora in a monophyletic clade, distant from the closely related fungi in the freshwater family Lindgomycetaceae. Pairwise LSU rDNA sequence alignment of the sexual/asexual morphs of L. aquatica are 99% similar. Lolia species are characterized by pseudothecial or stromatic, immersed to erumpent, dark-brown to black, coriaceous to sub-carbonaceous ascomata, cylindric-clavate, bitunicate, fissitunicate, short pedicellate asci, yellow to reddish-brown, phragmo- or dictyospores, surrounded by prominent gelatinous sheath. Lolia species are phylogenetically distant from the closely related genera: Leptosphaeria (Leptosphaeriaceae) and Massariosphaeria (Pleosporales incert. sed.). Lolia differs from Leptosphaeria in having a prominent large gelatinous ascospore sheath, while this is absent in Leptosphaeria species. Lolia differs from Massariosphaeria in having smaller ascospores and fewer transverse septa. Based on molecular data and morphology, a new species, Lolia dictyospora, is established.